The effect of Reminiscence on Elderly Hope - R Babaei; H Mahdiun; AM Nazari (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: Successful aging and life satisfaction accompanies with continued and high levels of hope in subsequent stages of life. This study examines the effect of reminiscence therapy on hope in elderly.  Material & Methods: It was a quasi-experimental study. A total of 24 elderly of Karaj city were randomly recruited among the elderly of Setayesh hospice and were voluntary assigned into experimental (n=12) and control (n=12) groups. Reminiscence therapy was performed during eight sessions for the experimental group. Hope was assessed in the two groups before and immediately after intervention by Snyder questionnaire. Data was analyzed by independent and pair T test using SPSS-PC (v. 21).   Results: There was a significant difference between experimental and control groups after intervention (P< 0.001). The mean score of hope in the experimental group was increased from 23.83±3.01 before intervention to 28.08±2.06 after the intervention (P= 0.000). Conclusion: According to the findings it can be said that reminiscence therapy increases elderly hope. Therefore using this simple, practical and inexpensive technique in hospices is recommended.